2023
DOI: 10.1111/ene.15742
|View full text |Cite
|
Sign up to set email alerts
|

High serum neurofilament light chain levels correlate with brain atrophy and physical disability in multiple sclerosis

Abstract: Background and purpose Serum neurofilament light chain (sNfL) is a promising biomarker of neuroaxonal damage in persons with multiple sclerosis (pwMS). In cross‐sectional studies, sNfL has been associated with disease activity and brain magnetic resonance imaging (MRI) changes; however, it is still unclear to what extent in particular high sNfL levels impact on subsequent disease evolution. Methods sNfL was quantified by an ultrasensitive single molecule array (Simoa) in 199 pwMS (median age = 34.2 years, 64.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Although NfL has classically been associated with WM tract damage, 5,6 which is in keeping with the results from the MPRAGE group, NfL had a weak relationship with GM volume loss in the FSPGR group. NfL associations with GM volume have been demonstrated in multiple sclerosis 27,28 . This may in part be driven by Wallerian degeneration of WM contributing to loss of GM or by an independent process 29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NfL has classically been associated with WM tract damage, 5,6 which is in keeping with the results from the MPRAGE group, NfL had a weak relationship with GM volume loss in the FSPGR group. NfL associations with GM volume have been demonstrated in multiple sclerosis 27,28 . This may in part be driven by Wallerian degeneration of WM contributing to loss of GM or by an independent process 29 …”
Section: Discussionmentioning
confidence: 99%
“…NfL associations with GM volume have been demonstrated in multiple sclerosis. 27,28 This may in part be driven by Wallerian degeneration of WM contributing to loss of GM or by an independent process. 29 A relative strength of our study is the use of biascorrected and accelerated 95% CIs, a conservative measure of significance.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline serum NfL levels have been associated with worsening of EDSS in the first year, number of relapses, and progression of brain atrophy, as measured by cerebral magnetic resonance imaging (MRI) [ 52 55 ] in short-term prognosis studies. Regarding long-term prognosis, both baseline and longitudinal measures of NfL levels have been linked to greater cerebral MRI-based brain atrophy [ 25 , 53 , 56 60 ]; however, their association with disability progression is inconsistent [ 23 ]. In fact, studies with longer clinical follow-up periods found no relationship between baseline NfL levels and disability progression [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%